Expression of Career Self-Efficacy of Students Enrolled In University Physical Education and Sports Study Programmes - Romualdas Malinauskas; Žilvinas Stankevičius (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  An  assumption  that  the  fourth-year  students  of  university  physical education and sports study programmes have greater career self-efficacy than the first-year students is made in the article. Research aim was to reveal peculiarities of the expression of the career self-efficacy of the students enrolled in university physical education and sports study programmes. Research methods. The random sample size consisted of 278 first and fourth-year full time students of physical education and sports study programmes from Lithuanian Sports University and Šiauliai University. Two methods were used to carry out the survey: Career Self-Efficacy Sources Scale (CSESS) and Career Decision-Making Self- Efficacy Scale-Short Form (CDMSE-SF). Research results. The research showed that there was a statistically significant difference (t (276) = -1.96; p < 0.05) between the first and fourth-year students of university physical education and sports study programmes in respect of the level of career self-efficacy. The fourth-year students were able to make a better use of occupational information (4.08 ± 0.54) than the first-year students (3.95  ± 0.56). It was determined that indicators of goal selection and career planning were higher (p < 0.05) in the case of the fourth-year students than in the case of the first-year students. Discussion and conclusions. It was determined that, in comparison with the first-year students, the career self- efficacy of the fourth-year students of university physical education and sports study programmes was more based (p < 0.05) on the following sources: vicarious experience, verbal persuasion and performance accomplishments. Comparison of the levels of career self-efficacy of the first and fourth-year students of university physical education and sports study programmes revealed that the fourth-year students had greater career self-efficacy (p  < 0.05) and that indicators of the components of their career self-efficacy - occupational information, goal selection and career planning were higher (p < 0.05) than those of the first-year students. Keywords: career education, self-efficacy, career self-efficacy, university studies, physical education and sports.